MENINGKATKAN KETERAMPILAN PASSING BAWAH MELALUI MODIFIKASI ALAT DAN MEDIA PADA SISWA KELAS V SDN 159 GRESIK - Marethoo Setyawan Putra, One; Sapto Wibowo; M. Rofi’i Zakaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to improve students' skills by applying modifications to their learning tools and media. The method used in this study is Classroom Action Research (PTK) with the Kemmis and McTaggart model which includes planning, action, observation and reflection, which consists of 2 cycles in the implementation of the research. The data collection techniques in this study are in the form of tests and non-tests, observation and documentation. The sample used in this study was 14 students in grade V of SDN 159 Gresik consisting of 2 male students and 12 female students. The results of the study can be seen starting from pre-cycle, students who complete as many as (35,71%) or 5 students. Then in the first cycle, the students who completed were (57,14%) or 8 students. Then in the second cycle, the students who completed were (85,71S%) or 12 students. The results of the study showed that there was a significant increase in each cycle. Thus, it can be concluded that by applying modifications of tools and media in learning volleyball bottom passing can significantly improve the skills of grade V students of SDN 159 Gresik in practicing volleyball bottom passing techniques.